A FORMATIVE EVALUATION OF SCHOOL - BASED MANAGEMENT IN PUBLIC SCHOOLS: AN ANALYSIS - MARTIN, MATRONILLO M. (International Journal of Psychosocial Rehabilitation, 2020)
The study intends to evaluate formatively the implementation of School-Based Management (SBM) in Alfonso Lista District 1 and 2, Division of Ifugao. The model employed in the study was Stufflebeam’s Context, Input and Process (CIP) to evaluate the implementation of SBM. The research method utilized was triangulation through the use of data analysis. The mean rating and thematic approach were used to determine the extent of SBM and elaborated themes. Results of the study showed that enrollment had an increasing trend, 0.53% dropout rate, 100% retention rate and a “moving towards mastery” achievement in achievement rate. The implementation of SBM was a moderate attainment of school objectives. Moreover, the involvement of the School Support Committee was only to a moderate extent including participative decision-making. Likewise, the operational aspects of SBM were not fully implemented by the school heads of both districts. Additionally, the contribution of school heads’ leadership and management in terms of participatory decision-making and control over staff management were manifested. The study delved on the improvement of schools’ decision making on policies and programs that should be implemented. This also caters on the needs to give quality education among students without sacrificing the quality services that should be rendered. Democratic ways of leadership in an institution supplemented with equality and equity as dealt with teachers and stakeholders.